Metabolic mechanisms of a drug revealed by distortion-free13C tracer analysis - Cha, J.W.; Jin, X.; Jo, S.; An, Y.J.; Park, S. (Royal Society of Chemistry, 2021)
Metabolomic isotopic tracing can provide flux information useful for understanding drug mechanisms. For that, NMR has the unique advantage of giving positional isotope enrichment information, but the current13C 1D NMR approach suffers from low sensitivity and high overlaps. We developed a new 2D heteronuclear NMR experiment incorporatingJ-scaling and distortion-free elements that allows for quantitative analysis of multiplets with high sensitivity and resolution. When applied to an old chemotherapeutic drug, the approach provided a quantitative estimation of TCA-cycle turns, confirming the conventional mechanism of its mitochondrial metabolic enhancement. Additionally, the approach identified a new mechanism of the higher contribution of the pentose phosphate pathway to serine synthesis in the cytosolic compartment, possibly explaining the broad pharmacological activities of the drug. Our approach may prove beneficial in helping to find new usages or metabolic mechanisms of other drugs. ？ The Royal Society of Chemistry 2021.